International Olympic Committee (IOC) consensus statement on acute respiratory illness in athletes part 1: acute respiratory infections. Issue 19 (21st July 2022) - Schwellnus, Martin; Adami, Paolo Emilio; Bougault, Valerie; Budgett, Richard; Clemm, Hege Havstad; Derman, Wayne; Erdener, Uğur; Fitch, Ken; Hull, James H; McIntosh, Cameron; Meyer, Tim; Pedersen, Lars; et al.
Abstract : Acute illnesses affecting the respiratory tract are common and form a significant component of the work of Sport and Exercise Medicine (SEM) clinicians. Acute respiratory illness (ARill) can broadly be classified as non-infective ARill and acute respiratory infections (ARinf). The aim of this consensus is to provide the SEM clinician with an overview and practical clinical approach to ARinf in athletes. The International Olympic Committee (IOC) Medical and Scientific Commission appointed an international consensus group to review ARill (non-infective ARill and ARinf) in athletes. Six subgroups of the IOC Consensus group were initially established to review the following key areas of ARill in athletes: (1) epidemiology/risk factors for ARill, (2) ARinf, (3) non-infective ARill including ARill due to environmental exposure, (4) acute asthma and related conditions, (5) effects of ARill on exercise/sports performance, medical complications/return-to-sport and (6) acute nasal/vocal cord dysfunction presenting as ARill. Several systematic and narrative reviews were conducted by IOC consensus subgroups, and these then formed the basis of sections in the consensus documents. Drafting and internal review of sections were allocated to 'core' members of the consensus group, and an advanced draft of the consensus document was discussed during a meeting of the main consensus core group in Lausanne, Switzerland on 11 to 12 October 2021. Final edits were completed after the meeting. This consensus document (part 1) focusses on ARinf, which accounts for the majority of ARill in athletes. The first section of this consensus proposes a set of definitions and classifications of ARinf in athletes to standardise future data collection and reporting. The remainder of the consensus paper examines a wide range of clinical considerations related to ARinf in athletes: epidemiology, risk factors, pathology/pathophysiology, clinical presentation and diagnosis, management, prevention, medical considerations, risks of infection during exercise, effects of infection on exercise/sports performance and return-to-sport guidelines.